How well do Australian government urban planning policies respond to the social determinants of health and health equity?. (December 2020) - McGreevy, Michael; Harris, Patrick; Delaney-Crowe, Toni; Fisher, Matt; Sainsbury, Peter; Riley, Emily; Baum, Fran
Highlights: All documents accept the links between urban environments and health and wellbeing. Health benefits often a secondary benefit of other goals. Objectives favour urban form that is compact, mixed use, walkable and transit oriented. Livability is a preeminent goal in most documents. The targeted nature of liveability improvements impedes health equity. Abstract: There is now wide recognition and evidence that the built environment affects population health and health equity. This research provides a thematic analysis of 108 urban planning policy documents from Australian state, territory, and federal governments to address the question: How well do Australian government urban planning policies respond to the social determinants of health and health equity? Health and health equity were discussed explicitly in several policies, most often as a secondary or co-benefit to environmental, social, and economic concerns. The most significant themes in the documents associated with health were visions for urban development that is compact, mixed use, walkable and transit oriented. These attributes are summed up in the term' liveable'. However, strategies to improve liveability were largely confined to areas targeted for residential infill and redevelopment, leaving car dependent and generally lower income, outer metropolitan areas potentially untouched. In addition, there were strategies that potentially conflicted with liveability, walkability, and transit orientation; the most notable being major road projects. This thematic analysis of Australian urban planning policies shows that some social determinants of health and health equity are being acted upon. However, policy conflicts and contradictions mean the policies are unlikely to deliver more healthy and equitable cities without further consideration of some of the structural issues likely to undermine healthy and equitable urban development.